(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2020)
The study’s findings, which looked at how students in Digital Enlivenment sought forinformation, are presented in this report. The survey’s objectives were to examine how university studentsutilize information technology to find information and how they access online resources. The researchmade an attempt to identify the specific sources of resource access. And the primary research topic wasConcept of Information, Information Seeking, Information Seeking Behavior, Information Need andSeeking, Information Seeking Behavior on the Internet, and Information Seeking Behavior in DigitalEnvironment.